THE ROLE OF INTELLIGENT TRANSPORTATION SYSTEMS (ITS) IN SUSTAINABLE SMART CITIES - Fedoruk, Illia (Sworld-Us Conference proceedings, 2025)
Intelligent Transportation Systems (ITS) are pivotal for developing sustainable smart cities, addressing critical challenges like traffic congestion, safety, and environmental impact. This article explores the key components of ITS, including adaptive tra